KEHIDUPAN ORANG TUA JOMPO DI PANTI SOSIAL (STUDI KASUS UPT PANTI SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH MARPOYAN DAMAI PEKANBARU) - Wulandari, Riyani; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
When a person has reached a ripe old age, and the children had already formed his own family, is off the responsibility on them, and he returned more free independent as at the time of his marriage permula. Obligations of parenting, finance, educate and supervise children no longer he did. Therefore, the problems of the elderly should be a concern of all of us, good government, public institutions as well as the community itself increasingly aging her age a person then they increasingly need a place to take cover and get the love Dear primarily from the family itself. But in reality many of the elderly which is deposited by his own family to the Workhouses, how social relationships with family, and anything like a funeral in feel elderly living in nursing, and even factors among those who are displaced. The problem in this study i.e., what are the factors or issues so that the elderly who still there is this family entrusts to nursing homes and also how much capacity the elderly in workhouses. In this study four elderly people who leave her family to the PSTWKK in Soweto who became the subject of the research because of economic problems, it does not wish to hassle family, the existence of a conflict or problem or misunderstanding with family, and also because it did not want the family to take care of her anymore. Liked or nice elderly living in nursing because of the availability of all facilities of the parlors and grief or sad because much of the family.Key Words: Elderly, Families, Nursing Homes